THE GENERAL AND THE SPECIFIC IN THE CORRELATION OF BOUNDARIES BETWEEN THE SUBJECT FIELDS OF POLITICAL ANALYSIS AND POLICY ANALYSIS - Рубанов, В. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2019)
The article presents the author’s views of such a problem of theory and methodology as the characteristics of essence of the boundaries between the subject fields of Political Analysis and Policy Analysis, and their correlation, both being basic sciences within the framework of political management. This problem has been scarcely explored as yet, but it is of great importance for the institutionalization of Political Analytics as a branch of science in Ukraine.The author points out the main reason of the above-mentioned problem remaining still a pending one, namely, the lack of conceptual completeness of certain categories of Political Science, such as «object», «subject», «method», and «topic» of research. The article contains a detailed view of a number of examples, illustrating different approaches of scholars to definitions of the very subject and object of Political Science. Special attention has been given to definition of «method» as one of the key categories in objective characterization of any branch of academic research as well as most important element in the process of comprehension and familiarization of a topic by the subject of research.The article traces the process of intentional comprehension of a method, the latter’s transformation into a specific method and procedures of scientific cognition. It looks logical that the participant of the research activities should work out, within the framework of their respective branch of knowledge, a particular method, which reflects the topic adequately. At the same time a researcher should creatively use the other branches’ methods while adapting them to specific subject matter of the researcher’s own particular branch. The object, subject, topics and methods of this particular branch, namely Political Science, must be clearly interpreted and defined. Supported by the said principles, the author maintains that Policy Analysis, though providing for optimization of the very process of expertise and analysis as an essential part in preparing, making, and implementation of political decisions, still its object of study is but relatively independent within the boundaries of Policy Analysis’ subject. That is why Political Analysis, not Policy Analysis, constitutes an integral structural element of Political Analytics. The former is the real basis not only for the science’s name, but also for system integrity of all its structural elements in the process of actual functioning.